Transparency in Utilization of School Operational Assistance Funds at SMAN 2 Gorontalo Utara - Noor Aini; Ellys Rachman; Andi Yusuf Katili (Formosa Journal of Applied Sciences, 2022)
This type of research is descriptive research with a qualitative approach. The aim of this research is to find out the transparency of the use of School Operational Assistance (BOS) funds at SMAN 2 Gorontalo Utara. The focus of research in this study is understanding technical guidelines, management procedures, preparation of reports. The results showed that the BOS management team's technical guidelines had not been fully implemented because not all of the BOS management team understood technical guidelines, the management procedures for the use of BOS funds had not run optimally, as seen by several program items not being met because the costs had been transferred to other programs so that several programs had experienced a shift. not in accordance with technical guidelines, preparation of reports has not run optimally because it does not comply with existing operational guidelines where the preparation of reports is only carried out by treasurers and school principals without involving the BOS management team.